1968
DOI: 10.3758/bf03342467
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose incentive shifts in the Skinner box with thirsty rats

Abstract: Guttman (1953) has reported that hungry rats, exposed in a .skinner box to changing sucrose concentrations (4, 8,16, and 32%) responded in a monotonically increasing fashion to the increasing concentrations. Tombaugh & Marx (1965) reported that thirsty rats on the other hand yield a rather different function relating bar pressing and sucrose concentrations (4,8, 32, and 64%) with less response strength at 32 and 64% than at 4 or 8%. The former study presented the different concentrations in counterbalanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1976
1976
1977
1977

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Similar relationships have also been found, when incentives were presented separately (forced-choice condition). Fooddeprived and/or water-satiated animals typically respond (barpress) more vigorously for increased sucrose solutions, while highly water-deprived animals either respond at similar rates to all incentives (water 64% sucrose) (Beck, 1963 ;Oakley, 1965;Rosen & Jacobs, 1968;Tombaugh, 1974) or develop faster rates to water (Beck & Ellis, 1966). Highly water-deprived animals would also begin to respond more vigorously to sucrose than water at the end of lengthy experimental sessions of 30 min (Rosen & Jacobs, 1968).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar relationships have also been found, when incentives were presented separately (forced-choice condition). Fooddeprived and/or water-satiated animals typically respond (barpress) more vigorously for increased sucrose solutions, while highly water-deprived animals either respond at similar rates to all incentives (water 64% sucrose) (Beck, 1963 ;Oakley, 1965;Rosen & Jacobs, 1968;Tombaugh, 1974) or develop faster rates to water (Beck & Ellis, 1966). Highly water-deprived animals would also begin to respond more vigorously to sucrose than water at the end of lengthy experimental sessions of 30 min (Rosen & Jacobs, 1968).…”
mentioning
confidence: 99%
“…Fooddeprived and/or water-satiated animals typically respond (barpress) more vigorously for increased sucrose solutions, while highly water-deprived animals either respond at similar rates to all incentives (water 64% sucrose) (Beck, 1963 ;Oakley, 1965;Rosen & Jacobs, 1968;Tombaugh, 1974) or develop faster rates to water (Beck & Ellis, 1966). Highly water-deprived animals would also begin to respond more vigorously to sucrose than water at the end of lengthy experimental sessions of 30 min (Rosen & Jacobs, 1968).Cohen and Oostendorp (1976) measured both forcedExperiment I in the present study was based on a thesis submitted by the second author in partial fulfillment of the requirements for a master's degree at the University of Windsor. The present report is based on a paper delivered at the Canadian Psychological Association meeting, Quebec City, Quebec, June 1975.…”
mentioning
confidence: 99%
“…Our higher sucrose concentrations, while highly waterlast two studies, however, failed to replicate earlier deprived animals either respond at similar rates to all findings that decreased deprivation led to increased cue incentives (water-64% sucrose concentration) (Beck, utilization. Therefore, the question remains as to 1963;Oakley, 1965;Rosen & Jacobs, 1968;Tombaugh, whether the two deprivation levels produce different 1974) or develop faster rates to water (Beck & Ellis, levels of thirst arousal in rats. In order to answer this 1966).…”
mentioning
confidence: 99%
“…Highly water-deprived animals would also begin to deprived animals in sucrose incentive preferences. This respond more vigorously to sucrose than water at the strategy for investigating water-deprivation differences end of lengthy experimental sessions of 30 min or more seemed useful to employ, since a substantive body of (Rosen & Jacobs, 1968). research has shown marked incentive preference differThe present experiment was conducted as follows.…”
mentioning
confidence: 99%